Enacting Phenomenological Gestalts in Ultra-Trail Running: An Inductive Analysis of Trail Runners’ Courses of Experience - Rochat, Nadège; Gesbert, Vincent; Seifert, Ludovic; Hauw, Denis (Frontiers in Psychology, 2018)
Using an enactive approach to trail runners’ activity, this study sought to identify and characterize runners’ phenomenological gestalts, which are forms of experience that synthesize the heterogeneous sensorimotor, cognitive and emotional information that emerges in race situations. By an in-depth examination of their meaningful experiences, we were able to highlight the different typologies of interactions between bodily processes (e.g., sensations and pains), behaviors (e.g., actions and strategies), and environment (e.g., meteorological conditions and route profile). Ten non-professional runners who ran an ultra-trail running race (330 km, 24,000 m of elevation gain) volunteered to participate in the study. Data were collected in two steps: (1) collection of past activity traces (i.e., race maps, field notes, and self-assessment scales) and (2) enactive interviews using the past activity traces in which the runners were invited to relive their experience and describe their activity. The enactive interviews were coded using the course-of-experience methodology to identify the phenomenological gestalts that emerged from activity and scaffolded the runners’ courses of experience. The results revealed that runners typically enact three phenomenological gestalts: controlling global ease, enduring general fatigue and experiencing difficult situations, and feeling freedom in the running pace. These phenomenological gestalts were made up of specific behaviors, involvements, and meaningful situated elements that portrayed various ways of achieving an ultra-endurance performance in the race situation. They also highlighted how runners enact a meaningful world by acting in relation to the fluctuations in physical sensations and environmental conditions during an ultra-trail race. Practical applications for preparation, race management and sports psychology interventions are proposed to enrich the existing recommendations. In conclusion, this approach provides new research perspectives by offering a more holistic grasp of activity in trail running through an in-depth analysis of athletes’ experience. In doing so, we may expect that runners can connect these typical gestalts to their own personal experiences and stories as trail runners in order to sustain a viable approach to their sport.